A new effective way to degrade methylene blue by introducing negative ions powder into Fe3O4/H2O2 system to accelerate Fe(III)/Fe(II) transformation - Xiangfen Zhang (IWA Publishing, 2021)
Negative ions powders (NIP) have been widely applied in many fields because of their natural electric field and far infrared radiation, especially in wastewater treatment. In this study, the NIP was first introduced into Fe3O4/H2O2 system to degrade methylene blue (MB). The MB removal was completely achieved at 5 h via a non-photochemical pathway and the degradation rate constant of this system is about 0.565 h−1, which is about 16 times higher than in Fe3O4/H2O2 Fenton-like system (0.035 h−1). In addition, the results of quenching experiments indicate that the electron (e−) and negative oxygen ion (•O2−) are the main reactive species. It was determined that Fe3O4@NIP is the effective component that leads to the activation of H2O2 to produce •OH, which derive from the pathway: NIP acts as an electron donor to reduce Fe(III) into Fe(II). Moreover, NIP can produce negative ions, which is also conductive to degradation. This study suggests a promising direction for the practical application of NIP based catalysis by integrating it with the Fe(III)/Fe(II) transformation process. HIGHLIGHTS The FTIR, XRD, and XPS spectra indicate that the chemical properties of NIP change after the precipitation-hydrothermal process.; The SEM revealed that Fe3O4 was uniformly dispersed in the composite.; The catalytic activity performance of the Fenton-like system was investigated to remove MB.;